Experimental determination of carbonate‐associated sulfate δ34S in planktonic foraminifera shells. (29th April 2014) - Paris, Guillaume; Fehrenbacher, Jennifer S.; Sessions, Alex L.; Spero, Howard J.; Adkins, Jess F.
Abstract Understanding the coupling of oxygen, carbon, and sulfur cycles in the past is critical for reconstructing the history of biogeochemical cycles, paleoclimatic variations, and oceanic chemistry. The abundance of sulfur isotopes (δ34S) in sulfate from ancient marine carbonates, or carbonate‐associated sulfate (CAS), is commonly used, along with other archives (mainly evaporites and barite), to estimate the δ34S of seawater throughout Earth history. Analyses of CAS from hand‐picked foraminifera are potentially valuable because this group of organisms is used in numerous paleoceanographic studies. They could provide coupled, high‐resolution records of δ13C, δ18O, and δ34S isotopic changes directly linked to orbitally tuned records of climate change through the Cenozoic. Such measurements have not previously been possible due to limitations of sensitivity in conventional IRMS‐based techniques. However, the recent development of CAS analysis by multicollector inductively coupled plasma mass spectrometry (MC‐ICP‐MS) now allows us to work on samples containing just a few nmol of sulfur with accuracy for δ34S values approaching 0.1‰ and, consequently, to analyze hand‐picked samples of foraminifera shells. Here we report the results of culture experiments with the planktonic species Orbulina universa, that establish a shell:seawater δ34S calibration for future applications to the fossil record. Our new method uses <650 μg of carbonate (∼15 shells) per analysis. The results show that S isotopes are fractionated consistently by −1‰ between seawater and O. universa tests. We also demonstrate that O. universa faithfully records the [SO42−]/[Ca2+] ratio of the seawater in which it grew.